(untitled) (Kampelmas, 2022)
The presence of this writing was motivated by the lack of interest and desire from the congregational mothers of Al-Huda Mosque located in Karangpetir Village, Kalimanah District, Purbalingga Regency, Central Java in reading the Qur’an. This writing refers to whether the takhsin program can be applied to the teaching and learning process in improving the ability to read the Qur’an in the mothers of the Al-Huda Mosque congregation. This writing method uses qualitative research and data obtained from observations, interviews, and documentation. Through the takhsin program, efforts to improve the ability to read the Qur’an of the women of the Al-Huda Mosque congregation obtained significant results. This means that mothers in reading the Qur’an using this method have increased, both in terms of makharijul letters, tajwid rules, gharaibul, qiraah and do not forget how mothers can glorify the Qur’an. When the explanation of the concept of reading the Qur’an does not forget to provide a distraction, every Muslim must have an attitude of glorifying the Qur’an and be able to choose a teacher to be used as a reference. In addition, in the teaching and learning process when delivering theory, educators immediately put it into practice. Then reviewed again the next day related to the material that has been delivered.